(untitled) (Indian Journal of Nematology, 2024)
PCN was intercepted in north India in the farm area of ICAR-Central Potato Research Institute (CPRI), Himachal Pradesh. CPRI being a nodal institution for the development of potato varieties/hybrids, a lot of germplasm and seed material exchange takes place between the institution and other Central/State Government agencies mandated to work on potato in the country. The basic seed produced at the farms of CPRI is multiplied at different Govt. Potato Seed Multiplication Farms (GPSMFs) of States/UTs, Departments of Agriculture Himachal Pradesh, Uttarakhand, and Jammu & Kashmir for further distribution to farmers in these and other states of the country. Considering the present scenario on the distribution of PCN in the three hilly states/UTs of North India, some general inferences can be drawn. (i) High populations of PCN were recorded at GPSMFs; this may be due to the continuous cropping of potato in these farms. Circumstantial evidence reveals the nematodes must have been introduced long ago, but due to nonspecific above-ground symptoms and lack of awareness, they could not be detected earlier. (ii) GPSMFs may be contributing towards the dissemination of PCNs to farmers’ fields, but the low populations in PCN-conducive areas could be due to discontinuous cultivation of potato crop. (iii) Populations of PCN at lower altitudes (<2000 m AMSL) may be G. pallida, wherever full cysts were encountered. The interception of empty cysts in such locations may be due to unfavourable temperatures for nematode development. The distribution pattern of PCNs in the northern hilly States/UTs in India vis-à-vis south India (the Nilgiris) shows contrasting patterns. While in the Nilgiris, most of the fields are infested, harbouring high cyst populations; the same is not valid in the north where such high populations are witnessed mostly in the GPSMFs. This leads to the assumption that PCN might have been introduced to the northern hilly states from the south much before the domestic quarantine regulations were enforced against them in 1971. However, independent and multiple introductions of seed potato (and PCN) from Europe is not ruled out. More intensive surveys are warranted to map the area for PCN completely. Further, similar geographies in the north-eastern parts of the country have not been surveyed so far for PCN and should be undertaken on priority.